Pengaruh Konsentrasi Pupuk hayati dan Dosis Pupuk NPK terhadap Pertumbuhan dan Hasil Tanaman Kangkung Darat (Ipomoea reptans) - Rina Husnawati; Aluh Nikmatullah; Novita Hidayatun Nufus; Herman Suheri (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
This study aims to determine the effect of the concentration of biofertilizer and the dose of NPK fertilizer and their interaction on the growth and yield of land kale plants. This research was conducted from January to February 2024 at Pengenjek Village, Jonggat District, Central Lombok Regency. The design used in this research is Factorial Randomized Group Design (RAK) consisting of 2 treatment factors, namely the concentration of biological fertilizer consisting of 3 levels, namely K0 (control), K1 (5 ml/L) and K2 (10 ml/L). While the second factor is the dose of NPK fertilizer consisting of 4 levels, namely D1 (1 g/plant = control) D2 (1.5 g/plant), D3 (2 g/plant), and D4 (2.5 g/plant) so that 12 treatment combinations are obtained. Each treatment consisted of 3 replicates so there were 36 experimental units. Observation data were analyzed using analysis of variance (analysis of variance) at the 5% level, treatments that were significantly different were further tested using the Honest Differences (BNJ) test at the 5% real level. The results showed that there was a real interaction between the concentration of biofertilizer and the dose of NPK fertilizer in affecting the number of plant leaves at the age of 28, 35 hst and the fresh weight of plant plants at 35 hst. Biofertilizer concentration as a single factor significantly influenced plant height at 28 and 35 hst, height increase rate, number of leaves at 28 and 35 hst, stem diameter at 28 and 35 hst, fresh weight and dry weight of plants. While the dose of NPK fertilizer as a single factor had a significant effect on plant height at 28 and 35 hst, number of leaves at 28 and 35 hst, stem diameter at 28 and 35 hst, fresh weight and dry weight. In this study, the best treatment combinations were 5 ml/L biofertilizer concentration and 1 g/plant NPK fertilizer dose and 10 ml/L biofertilizer concentration and 1 g/plant NPK fertilizer dose. while the best biofertilizer concentration treatments were 5ml/L and 10 ml/L and the best NPK 1 g/plant fertilizer dose treatment on the growth and yield of land kaleplants.